On the shape of the power spectra of intensity fluctuations of a laser beam crossing a vortex flame - Sherstobitov, M. V.; Sazanovich, V. M.; Tsvyk, R. Sh; Panov, D. I. (Proceedings of SPIE)
In this work, we used the data of a laboratory experiment on registration of fluctuations in the intensity of a laser beam passing through a vortex flame (model of a fire tornado) to calculate their power spectra. The nature of the decay of the power spectra in the high-frequency region was studied. The dominance of the two-scale decay of such spectra over the single-scale decay is established. The analysis carried out makes it possible to compare the results with the well-known Kolmogorov-Obukhov theory for estimating the turbulence parameters of the free atmosphere and to assume the presence of an inertial interval in the vortex flame.